Daptomycin to bone and joint infections and prosthesis joint infections: a systematic review - Telles,João Paulo (2019)
ABSTRACT Backgroud: Daptomycin has been used in bone and joint infections (BJI) and prosthesis joint infections (PJI) considering spectrum of activity and biofilm penetration. However, the current experience is based on case reports, case series, cohorts, and international surveys. The aim of this systematic review was to evaluate studies about daptomycin treatment efficacy in BJI/PJI compared to other antibiotic regimens. Methods: PubMed, LILACS, Scielo and Web of Science databases were searched for articles about daptomycin and treatment of BJI and PJI from inception to March 2018. Inclusion criteria were any published researches that included patients with BJI treated with daptomycin. Diagnosis of BJI was based on clinical, laboratory and radiological findings according to IDSA guidelines. Results: From 5107 articles, 12 articles were included. Only three studies described the outcomes of patients with BJI treated with daptomycin with comparator regimen (vancomycin, teicoplanin and oxacillin). Studies presented large heterogeneity regarding device related infections, surgical procedures, and daptomycin regimens (varied from 4 mg/kg to 10 mg/kg). A total of 299 patients have been included in all studies (184 infections associated with orthopedic disposal and 115 osteomyelitis/septic arthritis). Two hundred and thirty-three patients were treated with daptomycin. The clinical cure rates on device related and non-device related infections (i.e. osteomyelitis) were 70% and 78%, respectively. Compared to all regimens evaluated, daptomycin group outcomes were non-inferior. Conclusion: Although a randomized clinical trial is needed, this systematic review tends to support daptomycin usage for bone and joint infections.